Pengaruh Budaya Organisasi dan Pemberdayaan terhadap Komitmen Organisasi dalam Meningkatkan Kinerja - Pratiwi, Putri (Jurnal Ilmiah Aset, 2012)
The purpose of this study was to determine the influence of organizational culture on organizational commitment, the influence of employee empowerment on organizational commitment, the influence of organizational culture on employee performance, the effect of empowerment on employee performance and the influence of organizational commitment to employee performance. This studys population was employees. This study used survey methods, sampling and questionnaires as primary data collection tool. The sample used was simple random sampling. The samples used as many as 109 respondents with data analysis using Structural Equation Modeling (SEM). The results showed that there was significant influence of organizational culture and employee empowerment on organizational commitment whereas the level of the organizational culture variables, variable of employee empowerment and organizational commitment were less in affecting employee performance variables.